Pelatihan Pengoperasian Website Berbasis Wordpress Dalam Mendukung Pemasaran Digital Pada Boesa Management Medan - Tambunan, Sarah Rouli; Siagian, Desmon Gunadi; Rismawati; Manurung, John Sihar (Politeknik Negeri Medan, 2024)
A regularly updated website is essential to support marketing activities in today's digital era. This is what underlies Boesa Management's efforts to improve the performance of its website in order to increase company credibility, expand market reach, and access information. However, the lack of team member skills in website operation makes the company rely on third parties so that it is not free and slow in managing information on the website. Therefore, the Polmed service team took the initiative to provide WordPress-based website operation training to Boesa Management employees by bringing in professionals in the field of web design. Through this training, employees are expected to have qualified skills in website operation so that the company can be independent in managing all information on the company website.